2015
DOI: 10.4238/2015.august.14.12
|View full text |Cite
|
Sign up to set email alerts
|

Effects of washed platelets vs platelet-rich plasma on the proliferation and mineralization of rat dental pulp cells

Abstract: ABSTRACT. We examined the effects of washed platelets (WPLTs) and platelet-rich plasma (PRP) on the proliferation and mineralization of rat dental pulp cells. Rat dental pulp cells were separated, cultured, and identified. Medium containing 1, 10, 100, or 500 mL/L PRP or WPLTs was added to 4th generation cells. The MTS method was used to determine cell proliferation. Alizarin red staining was used to observe the formation of mineralized nodules after cell mineralization and induction for 10 and 20 days under d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…We used low concentrations of CGF extract to mimic the sustained release feature in vivo , and the immunoregulatory effects of 20 and 50% CCM were not significantly different in most experiments. Consistent with our study, previous studies have shown that CGF extract modulated cell differentiation at relatively low concentrations (5–50%), and higher concentrations exerted no or negative effects [ 29 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…We used low concentrations of CGF extract to mimic the sustained release feature in vivo , and the immunoregulatory effects of 20 and 50% CCM were not significantly different in most experiments. Consistent with our study, previous studies have shown that CGF extract modulated cell differentiation at relatively low concentrations (5–50%), and higher concentrations exerted no or negative effects [ 29 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…A few studies pointed out that PRP could improve odontogenic/osteogenic differentiation [13,34,35] and mineralization [11,12] of dental stem cells. PRP promoted mRNA and protein expression of DSPP and DMP-1 in SCAP [13].…”
Section: Discussionmentioning
confidence: 99%
“…PRP is a favorable autologous scaffold that can facilitate cell proliferation and differentiation [10]. Dental pulp stem cells (DPSCs) cultured with a certain concentration of PRP exhibited preferable proliferation, migration, and mineralization [11,12]. SCAP cultured with PRP expressed a high level of odontogenic markers such as dentin matrix protein 1 (DMP-1) and dentin sialophosphoprotein (DSPP) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, similar phenomenon was observed in the mineralization process of rat dental pulp cells when induced under different concentrations of PRP. 28 Qin et al 18 suggested that it may be associated with the unsuitable pH of culture medium resulting from containing too much platelets. We thought that the high level of leukocytes, interleukin (IL)-1β, and IL-6 might be responsible for the negative role of high-dosage CGF as well.…”
Section: Discussionmentioning
confidence: 99%